Evaluation of the Quebec Community Health and Social Service Foundation's (QCHF) Patient Navigator Project - Anastasopoulos, Vanessa (2021)

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

Vitality - Community Health and Social Services Network (CHSSN) (2019)
Keywords: Official Language Minority Community (OLMC)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

2015 CHSSN-CROP Survey on Community Vitality : Findings on English-speaking Community Vitality Across Key Sectors - Pocock, Joanne (Community Health and Social Services Network, 2016)
This 2015-2016 Baseline Data Report relays key findings of the 2015 CHSSN/CROP Survey on Community Vitality as they unfold across key sectors. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income and level of bilingualism. This report from the 2015 survey is intended as a companion to the 2015-2016 Baseline Data Report entitled English Language Access to Health and Social Services in Québec, which includes a summary of results from Focus Group sessions conducted in several regions around the province.

Accès interrégional aux services sociaux et de santé pour les personnes d'expression anglaise de l'est de Québec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

Inter-regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

Inter-Regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This project was developed to better understand the experience and needs of English speakers from the eastern regions of Quebec (Gaspésie - Îles-de-la-Madeleine, the North Shore, including the Lower North Shore, and the Lower Saint-Lawrence) as concerns extra-regional health and social services. The specific challenges facing this official language minority community were known only anecdotally, but needed to be better understood before effective action could be taken to address the needs of this population.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)